The House at Watch Hill : The Watch Hill Trilogy #1 - Moning, Karen Marie (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2024)
"Zo Grey is reeling from the sudden death of her mother when she receives a surprising call from an attorney in Divinity, Louisiana, with the news she has been left an inheritance by a distant relative, the terms of which he will only discuss in person. Destitute and alone, with nothing left to lose, Zo heads to Divinity and discovers she is the sole beneficiary of a huge fortune and a monstrosity of a house that sits ominously at the peak of Watch Hill but she must live in it, alone, for three years before the house, or the money, is hers. Met with this irresistible opportunity to finally build a future for herself, Zo puts aside her misgivings about the foreboding Gothic mansion and the strange circumstances, and moves in, where she is quickly met by a red-eyed Stygian owl and an impossibly sexy Scottish groundskeeper. Her new home is full of countless secrets and mystifying riddles, with doors that go nowhere, others that are impossible to open, and a turret into which there is no visible means of ingress. And the townspeople are odd What Zo doesn t yet know is that her own roots lie in this very house and that in order to discover her true identity and awaken her dormant powers, she will have to face off against sinister forces she doesn t quite comprehend or risk being consumed by them."-- Provided by publisher.
new book 2024 fall.
Keywords: Witches -- Fiction; Vampires -- Fiction; Inheritance and succession -- Fiction; Grief -- Fiction; Man-woman relationships -- Fiction; Louisiana -- Fiction; Witch fiction; Paranormal fiction; Novels; Gothic fiction; Vampire fiction; Romance fiction; Fantasy fiction